THE IMPLICATION OF GREEN ENTREPRENEURSHIP AND GREEN INNOVATION TO ENHANCE SMES' PERFORMANCE - Putra, Pasca Dwi; Zainal, Andri; Harahap, Khairunnisa; Agusti, Ivo Selvia; Saputra, Hendra; Thohiri, Roza; Afrida, Fenny (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This study looks into how starting businesses with eco-friendly ideas and creating new green technologies can affect the success of small and medium-sized enterprises. The research was conducted using quantitative and direct survey methods with a sample of 103 MSMEs. After evaluating model fit, hypothesis testing procedures were performed using Structural Equation Modeling (SEM). Throughout the study timeframe, the impact of green entrepreneurship on green innovation was significant. Nonetheless, no statistical correlation was found between green entrepreneurship and the performance of MSMEs. This research discovered that green entrepreneurship positively and significantly influences green innovation. Nevertheless, this effect did not affect the performance of MSME businesses. Numerous studies demonstrate that adopting sustainable business practices can enhance the performance of MSMEs. Conversely, the findings show a significant effect of green innovation on achieving MSMEs. The implications of this research are a reference for MSMEs. They can use this to improve their performance and have a competitive advantage.